Changing Role of Tamang Women at Household Level in Mahalaxmi Municipality-10, Lalitpur (Research Nepal Journal of Development Studies, 2025)
This study analyzed the changing role of Tamang women at the household level in Mahalaxmi Municipality-10 (Lakuri-Bhanjyang), Lalitpur. The study explored their socio-economic situation, their changing role in improving family livelihoods, and their perceptions of these changes. The research used a convergent parallel mixed-methods approach, combining a household survey of 120 families with in-depth narrative interviews with nine Tamang women and three local elected representatives. The data reveal a community in significant transition. Households are moving away from a traditional agriculture-based occupation due to small landholdings and food insecurity, shifting instead towards diversified cash-based livelihoods like business, wage labor, and tourism. Within this transition, Tamang women are becoming central figures and change agents in their family and community. Their roles have expanded beyond subsistence agricultural work to become key managers of household finances and operations of local shops and business. They actively participate in informal savings groups, make important decisions about children's education and daily expenses, and contribute to cash income. While this grants them greater economic agency and dignity, their control over major assets like land remains limited, and their political engagement is very low. The Tamang women perceived their changing role as a move towards modernity and improved family livelihoods, yet they also expressed concern about the erosion of the Tamang language and culture. The study concludes that the changing role of Tamang women is a story of adaptive resilience, as they navigate new economic realities while balancing aspirations for progress with a desire to preserve their cultural identity. The study thus recommends supporting women through formalized cooperatives, legal literacy, and skill training, while urging local government to implement gender-sensitive policies and initiatives that both promote economic opportunity and safeguard cultural heritage.